2019
DOI: 10.29333/ejgm/93478
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the frequency of dental caries in asthmatic children under treatment with inhaled corticosteroids and healthy children in Sabzevar in 2017-2018

Abstract: Background and Objective:Regarding the prevalence of premature dental caries in childhood and the role of asthma as a risk factor for increased vulnerability to dental caries, the present study aimed to determine and compare the frequency of dental caries between asthmatic children under treatment with inhaled corticosteroids and healthy children. Methodology: In this case-control study, 70 children with asthma who were taking corticosteroid sprays for at least one year and 70 healthy children aged 3-12 visiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 18 publications
0
2
0
1
Order By: Relevance
“…A study of Shulman et al discover that adolescents with severe AD with permanent teeth had lower DMFT and fewer carious lesions than systemically healthy controls, but the same relationship was not significant in children with primary dentition [25]. Hassanpour et al (2019) have found a higher mean DMFT in patients with AD than in a healthy group (p < 0.05) [26]. This finding supports the results of the paper showing that patients with AD who used inhaled corticosteroids were 6.4 times (OR = 6.41, 95% CI 1.88-21.08, p = 0.003) more likely to have carious lesions than patients who did not use inhaled corticosteroids.…”
Section: Discussionmentioning
confidence: 99%
“…A study of Shulman et al discover that adolescents with severe AD with permanent teeth had lower DMFT and fewer carious lesions than systemically healthy controls, but the same relationship was not significant in children with primary dentition [25]. Hassanpour et al (2019) have found a higher mean DMFT in patients with AD than in a healthy group (p < 0.05) [26]. This finding supports the results of the paper showing that patients with AD who used inhaled corticosteroids were 6.4 times (OR = 6.41, 95% CI 1.88-21.08, p = 0.003) more likely to have carious lesions than patients who did not use inhaled corticosteroids.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, salivary flow reduction and dry mouth are some of the side effects related to the use of inhaled drugs (Smidt et al, 2010). Studies have been demonstrating lack of consistency in the use of inhaled corticoid and its relation with dental caries especially in asthmatic patients, but Hassanpour et al (2019) found a higher mean of dmft in asthmatic patients than healthy group (p < 0.05) (Hassanpour et al, 2019;Mohamed et al, 2015). This result supports the finding of our work, which demonstrated that patients with AD that used inhaled corticoid were 6.4 times (OR = 6.41; p = 0.003, 95% CI: 1.88-21.08) more likely to have caries than patients that did not use inhaled corticoid.…”
Section: Ta B L E 1 (Continued)mentioning
confidence: 99%
“…У детей 9-12 лет, страдающих БА, распространенность кариозного процесса наиболее выражена при тяжелой степени заболевания [17]. Тяжесть кариеса зубов и заболеваний пародонта находится в прямой зависимости от степени тяжести БА и АтД [18][19][20][21]. Исследования показали, что распространенность кариеса у детей и подростков с аллергической патологией достигает 90-100% [22,23].…”
unclassified